STATUS KEBERSIHAN GIGI DAN MULUT SISWA SMA NEGERI 9 MANADO PENGGUNA ALAT ORTODONTIK CEKAT - Momongan, Ravenske E. C; Lampus, Benedictus S.; ., Juliatri (Universitas Sam Ratulangi, 2015)
Abstract: Fixed orthodontic appliance has been widely used in society, but they are often not aware of the risk of the use of fixed orthodontic appliances such as dental and oral hygiene problems. Design tool fixed orthodontic makethe dental cleaning procedure becomes more difficult. Oral hygiene is maintained in the user less dental appliance, such as the user orthodontic appliances can cause periodontal tissue damage and increasing the number of caries during treatment. This study is a descriptive study in order to determine the status of oral and dental hygiene students of Public Senior High School 9 Manado users fixed orthodontic appliances. The study population is the students of Public Senior High School 9 Manado fixed orthodontic appliance users who were attending school classes XI and XII. Samples numbered 39 people and sampling carried out with total sampling method. The research instrument was a check list form and interview. Assessment of dental and oral hygiene status was obtained by measuring the score Simplified Oral Hygiene Index (OHI-S). The results showed that the average of OHI-S scores in SMA Negeri 9 Manado was 1,22. By sex as much as 3 boys (7,7%) had a score of OHI-S 0,83 and a total of 36 girls (92,3%) had a score of OHI-S 1,23; based on the socio-economic level as much as 6 students (15,4%) with moderate socioeconomic level had OHI-S score of 1,97 and a total of 33 students (84,6%) in the high socioeconomic level had OHI-S score of 1,06. Period of <1 year usage by 25 students (64,1%) had a score of OHI-S 1.05; 1-2 years as many as 12 respondents (30.8%) had a score of OHI-S 1,15 and >2 years two respondents (5, 1%) had a score of OHI-S 1.5.Oral hygiene status of the student-sex male and female average is fair. Oral hygiene statuses of students with socio-economic level of parents are on average quite good and students with low socioeconomic level average moderate. Oral hygiene status of students who use a fixed orthodontic appliance under 1 year and 1-2 years on average quite good and more than 2 years on average moderate. Oral hygiene status of the student users fixed orthodontic appliances in general quite good. Keywords : Fixed orthodontic, dental and oral hygiene.Abstrak: Alat ortodontik cekat sudah banyak digunakan dalam masyarakat, namun mereka sering tidak menyadari risiko penggunaan alat ortodontik cekat seperti masalah kebersihan gigi dan mulut. Desain alat ortodontik cekat menyebabkan prosedur pembersihan gigi dan mulut menjadi lebih sulit. Kebersihan gigi dan mulut yang kurang terjaga pada pengguna dental appliance, seperti pada pengguna alat ortodontik dapat menyebabkan kerusakan jaringan periodontal dan meningkatnya jumlah karies selama perawatan. Penelitian ini merupakan penelitian deskriptif dengan tujuan untuk mengetahui status kebersihan gigi dan mulut siswa SMA Negeri 9 Manado pengguna alat ortodontik cekat. Populasi penelitian yaitu siswa SMA Negeri 9 Manado pengguna alat ortodontik cekat yang duduk dibangku sekolah kelas XI dan XII. Sampel berjumlah 39 orang dan pengambilan sampel dilakukan dengan metode total sampling. Instrumen penelitian berupa formulir check list dan wawancara. Penilaian status kebersihan gigi dan mulut diperoleh dengan pengukuran skor Oral Hygiene Index Simplified (OHI-S). Hasil penelitian menunjukkan skor OHI-S rata-rata siswa SMA Negeri 9 Manado sebesar 1,22. Berdasarkan jenis kelamin sebanyak 3 siswa laki-laki (7,7%) memiliki skor OHI-S 0,83 dan sebanyak 36 siswa perempuan (92,3%) memiliki skor OHI-S 1,23; berdasarkan tingkat sosial ekonomi sebanyak 6 siswa (15,4%) dengan tingkat sosial ekonomi sedang memiliki skor OHI-S 1,97 dan sebanyak 33 siswa (84,6%) pada tingkat sosial ekonomi tinggi memiliki skor OHI-S 1,06. Lama penggunaan < 1 tahun sebanyak 25 siswa (64,1%) memiliki skor OHI-S 1,05; 1 ? 2 tahun sebanyak 12 responden (30,8%) memiliki skor OHI-S 1,15 dan > 2 tahun ada 2 responden (5, 1%) memiliki skor OHI-S 1,5. Status kebersihan gigi dan mulut siswa berjenis kelamin laki-laki dan perempuan rata-rata tergolong baik. Status kebersihan gigi dan mulut siswa dengan tingkat sosial ekonomi orang tua sedang rata-rata tergolong baik dan siswa dengan tingkat sosial ekonomi rendah rata-rata tergolong sedang. Status kebersihan gigi dan mulut siswa yang menggunakan alat ortodontik cekat di bawah 1 tahun dan 1- 2 tahun rata-rata tergolong baik dan lebih dari 2 tahun rata-rata tergolong sedang. Status kebersihan gigi dan mulut siswa pengguna alat ortodontik cekat pada umumnya tergolong baik.Kata kunci: alat ortodontik cekat, kebersihan gigi dan mulut.